Improving the Speech of Primary Class Students in Mother Language and Reading Literacy Lessons (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article discusses the development of speech skills of primary school students. Tasks related to free and effective, meaningly, full expression of students’ thoughts in written and oral form have been developed, including the importance of tasks related to the development of students’ speech in the primary grades, including the mother tongue and the science of reading, and the formation of students’ speaking skills through this.